Avaliação in vivo e in vitro dos efeitos antidepressivo e citoprotetor da Riparina IV em modelo de neuroinflamação induzido por lipopolissacarídeo de Escherichia coli - Capibaribe, Victor Celso Cavalcanti (2024)
Depression is one of the most common and recurrent psychiatric disorders, potentially severely debilitating for patients. It is clinically characterized by prolonged depressed mood, often accompanied by low self-esteem, pain, sleep or appetite disturbances, and suicidal ideation. Evidence suggests a significant role of neuroinflammation in the etiology and progression of this disorder, with astrocytes playing a fundamental role in this context. These cells possess Toll-Like Receptor 4 (TLR4) which, when sensitized to Lipopolysaccharide (LPS), trigger an inflammatory cascade with the aid of the MD-2 protein, leading to the release of pro-inflammatory cytokines resulting in a neuroinflammatory state. Considering the importance of seeking new therapeutic targets for depression treatment, this study investigates the role of riparin IV (RIP IV), a substance previously demonstrated to possess various activities, including antiinflammatory and antidepressant effects in animal models. The objective of this work is to evaluate the potential effects of RIP IV on depression in the context of the neuroinflammatory cascade triggered by LPS in animals, targeting the TLR4/MD-2 complex. Experiments were conducted on male C57BL/6 mice subjected to systemic administration of LPS (0.5mg/kg) for 10 days, and treated from the 5th day with RIP IV (50mg/kg), saline (0.9%), and escitalopram (10mg/kg). In silico (molecular docking), in vivo (behavioral), and in vitro (cell viability and cytotoxicity) tests with astrocytes were performed. The results show that RIP IV demonstrated binding affinity to the MD-2 portion similar to the antagonist ERI, indicating a possible interaction with the MD-2 complex. RIP IV exhibited antidepressant-like activity in the forced swim test, sucrose preference test, and splash test, as well as anxiolytic activity in the elevated plus maze and open field test in animals previously treated with LPS. No significant changes were observed in the hole-board and Y-maze tests. In vitro tests showed RIP IV cytotoxicity studies, with three concentrations selected after the MTT assay: 15.62, 7.81, and 3.90 μM. Evaluation of cell death revealed the necrotic process caused by LPS and the cytoprotective effect of RIP IV. Based on the demonstrated cytoprotective and antidepressant-like effects, as well as the potential similar binding with an MD-2 antagonist, RIP IV appears to be a relevant molecule, and future studies may culminate in the availability of a new therapeutic alternative for major depressive disorder.